2011
DOI: 10.1016/j.etp.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia of the lymphoepithelium of NALT in rats but not in mice upon 28-day exposure to 15ppm formaldehyde vapor

Abstract: perplasia of the lymphoepithelium of NALT in rats but not in mice upon 28-day exposure to 15 ppm formaldehyde vapor. Experimental and Toxicologic Pathology, Elsevier, 2010, 63 (1-2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Kuper et al (2009) examined the proliferative effect of formaldehyde on the NALT and local lymphnodes in F344 rats and B6C3F1 mice exposed to 0, 0.5, 1, 2, 6, 10, and 15 ppm formaldehyde for 28 days. The authors found an increased proliferation rate in the nasal epithelial cells and a slight to moderate simple hyperplasia of the NALT in rats exposed to 15 ppm but not at lower concentrations, and no increases were observed at any concentration in mice, suggesting that at concentrations of less than 15 ppm formaldehyde, sufficient levels of formaldehyde do not move beyond the nasal mucosa to the NALT to induce cell proliferation.…”
Section: Weight Of Evidence Regarding a Plausible Mode Of Action Fmentioning
confidence: 99%
“…Kuper et al (2009) examined the proliferative effect of formaldehyde on the NALT and local lymphnodes in F344 rats and B6C3F1 mice exposed to 0, 0.5, 1, 2, 6, 10, and 15 ppm formaldehyde for 28 days. The authors found an increased proliferation rate in the nasal epithelial cells and a slight to moderate simple hyperplasia of the NALT in rats exposed to 15 ppm but not at lower concentrations, and no increases were observed at any concentration in mice, suggesting that at concentrations of less than 15 ppm formaldehyde, sufficient levels of formaldehyde do not move beyond the nasal mucosa to the NALT to induce cell proliferation.…”
Section: Weight Of Evidence Regarding a Plausible Mode Of Action Fmentioning
confidence: 99%